Analisis Disiplin Kerja, Pelatihan dan Kinerja Karyawan pada CV. Balong Karya Utama - Apriyani; Aji Tuhagana; Zenita Apriani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to determine and analyze work discipline, training and employee performance at CV. Balong Karya Utama. This research method uses qualitative methods with descriptive explanations. Participants in this research were leaders and employees. The data analysis techniques in this research are information collection, data reduction, data presentation and drawing conclusions. The research results show that work discipline CV. Balong Karya Utama still has shortcomings that impact employee performance. Then the training has been effective, but there are still several obstacles related to employee attendance during training. Meanwhile, employee performance is influenced by several factors, namely work discipline and training, therefore the leadership of CV. Balong Karya Utama needs to pay attention to work discipline and employee training so that employee performance can improve.